Over-Expression of Catalase in Myeloid Cells Confers Acute Protection Following Myocardial Infarction - Cabigas, E. Bernadette (Molecular Diversity Preservation International (MDPI), 2014)
Cardiovascular disease is the leading cause of death in the United States and new treatment options are greatly needed. Oxidative stress is increased following myocardial infarction and levels of antioxidants decrease, causing imbalance that leads to dysfunction. Therapy involving catalase, the endogenous scavenger of hydrogen peroxide (H(2)O(2)), has been met with mixed results. When over-expressed in cardiomyocytes from birth, catalase improves function following injury. When expressed in the same cells in an inducible manner, catalase showed a time-dependent response with no acute benefit, but a chronic benefit due to altered remodeling. In myeloid cells, catalase over-expression reduced angiogenesis during hindlimb ischemia and prevented monocyte migration. In the present study, due to the large inflammatory response following infarction, we examined myeloid-specific catalase over-expression on post-infarct healing. We found a significant increase in catalase levels following infarction that led to a decrease in H(2)O(2) levels, leading to improved acute function. This increase in function could be attributed to reduced infarct size and improved angiogenesis. Despite these initial improvements, there was no improvement in chronic function, likely due to increased fibrosis. These data combined with what has been previously shown underscore the need for temporal, cell-specific catalase delivery as a potential therapeutic option.